Migracja, pamięć, tożsamość. „Nasza przemoc, wasza przemoc” Olivera Frljicia - Rewerenda, Magdalena (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2021)
MIGRATION, MEMORY, IDENTITY. OUR VIOLENCE AND YOUR VIOLENCE BY OLIVER FRLJIĆ The article is an analysis of the performance of Our Violence and Your Violence by Oliver Frljić through the prism of the important role the immigrants play in the process of shaping Polish national identity. It discusses the most crucial scenes which gained a lot of attention and led to protests held by the conservative circles during the presentation of the play during the 2016 edition of the Festival Premier in Bydgoszcz. The aforementioned scenes are interpreted in the context of the myth of the European Christian culture, the economic and symbolic dominance of the West over the East, the concept of the imaginary East, the phenomenon of enemy construction, and forced assimilation. The analysis also encompasses specific strategies employed by Oliver Frljić as a director, such as blurring the boundary between fiction and reality, playing with actors’ biographies, directly addressing the audience, and incorporating symbols referring to cultural, national, and religious identity. It also comments on social and artistic consequences of such artistic choices. The article reflects on the specific context of a scandal following the performance in Poland, the country hardly affected by the refugee crisis and where Muslim immigrants, despite their virtual absence, function as a bogeyman, a threatening figure of an immigrant-terrorist. The analysis of both Frljić’s performances and audience’s reaction to them reflect the way in which Polish national identity is simultaneously constructed in the relation to the figure of an aggressor and based on the perception of Poland as a victim, which is additionally fuelled by collective traumas of suffered — and often imagined — damages. Through analysing the theatrical performance, the article demonstrates that the (non)existence of the Stranger not only perpetuates harmful and excluding stereotypes, but also consolidates the collective identity of the nation. MIGRACJA, PAMIĘĆ, TOŻSAMOŚĆ. NASZA PRZEMOC, WASZA PRZEMOC OLIVERA FRLJICIA Artykuł stanowi analizę spektaklu Nasza przemoc, wasza przemoc w reżyserii Olivera Frljicia z perspektywy roli imigrantów z krajów muzułmańskich w procesie kształtowania polskiej tożsamości narodowej. Omawia kluczowe sceny, które wzbudziły protesty środowisk prawicowych podczas prezentacji przedstawienia podczas Festiwalu Prapremier w Bydgoszczy w 2016 roku w kontekście tematów takich jak: mit europejskiej kultury chrześcijańskiej, ekonomiczna i symboliczna dominacja Zachodu nad Wschodem, wyobrażony Wschód, wytwarzanie wroga czy przymus asymilacji. Analiza uwzględnia również specyficzne strategie reżyserskie Frljicia takie jak zacieranie granicy między prawdą i fikcją, gra z biografiami aktorów, bezpośrednie zwroty do publiczności czy odwołania do symboli odnoszących się do kulturowej, narodowej i religijnej tożsamości oraz artystyczne i społeczne konsekwencje tych zabiegów. Omówienie uwzględnia także specyficzny kontekst skandalu towarzyszącego pokazom w Polsce, gdzie kryzys uchodźczy praktycznie nie istnieje (z racji nieobecności emigrantów z krajów muzułmańskich), ale obecny jest podsycany lęk przed sfantazmatyzowaną figurą Muzułmanina-terrorysty. Analiza zarówno spektakli Frljicia, jak i ich recepcji wskazuje na sposób, w jaki kształtowana jest polska tożsamość narodowa: w antagonistycznej relacji do agresora, w oparciu o martyrologiczną pozycję Polski jako ofiary, wzmacnianą przez serię zbiorowych traum i pamiętanie krzywd — tych doświadczonych (i wyobrażonych), a nie wyrządzanych. Artykuł, bazując na kwestiach wypływających ze spektaklu teatralnego, pokazuje, jak (nie)obecność „obcego” nie tylko umacnia przemocowe i wykluczające stereotypy, ale także konsoliduje tożsamość zbiorową.